Determination of sensitivity to antibiotics of Campilobacter jejuni and Campilobacter coli isolated from human feces - Tambur Zoran; Miljković-Selimović Biljana; Bokonjić Dubravko (Vojnosanitetski Pregled)
Background/Aim. One of the most important bacterial zoonosis is campylobacteriosis. Human disease is mostly caused by thermophilic Campylobacter spp: Campylobacter jejuni (C. jejuni), Campylobacter coli (C. coli), Campylobacter lari (C. lari) and Campylobacter upsaliensis (C. upsaliensis). Campylobacteriosis is a mild and self-healing disorder. In patients with more severe and prolonged forms, an antibiotic treatment is recommended. Recommended drugs are erythromycin, ciprofloxacin, tetracyclin, chloramphenicol and ampicillin. Lately, an increase of Campylobacter genus resistance to antibiotics mostly used in therapy is an annoying evidence. The rise coincided with the beginning of antibiotic use, especially quinolones, in veterinary medicine. The aim of the study was to isolate and identify thermophilic Campylobacter spp. from human feces and to determine their sensitivity to antibiotics and hemotherapeutics mostly used in campylobacteriosis treatment. Methods. Sensitivity to erythromycin, tetracyclin, ampicillin, chloramphenicol and ciprofloxacin of 24 strains of Campylobacter spp. isolated from humans was investigated by E-test. Results. Seventeen C. jejuni and seven C. coli strains were investigated. Six (25%) out of 24 C. jejuni and C. coli investigated strains were resistant to ampicillin and seven (29.2%) were resistant to tetracycline. Twelve (50%) C. jejuni and C. coli investigated strains were resistant to ciprofloxacin. C. jejuni was more resistant (52.9%). Four (23.5%) C. jejuni strains were resistant to erythromycin and 11.7% to choramphenicol. None of C. coli strains were resistant to both chloramphenicol and erytromycin. Conclusons. Testing sensitivity to erythromycin, tetracycline, ampicillin, chloramphenicol and ciprofloxacin demonstrated a rather high resistance frequency of C. jejuni and C. coli strains isolated from humans. C. jejuni strains were more resistant than those of C. coli.